PEMBINAAN ROHANI DAN MOTIVASI BERWIRAUSAHA BAGI ANAK YATIM DAN DHUAFA PADA BULAN MUHARRAM BERSAMA LAZIS SABILILLAH MALANG - Yuyuk Liana; Dyah Aruning Puspita; Hanif Mauludin; Aminul Amin; Evi Maria; Bunyamin Bunyamin; Siti Munfaqiroh (P3M Politeknik Negeri Malang, 2021)
Muharram month is the month for Muslims to maximize their practice by sharing with others. For this reason, the service team of STIE Malangkucecwara together with Lazis Sabilillah Malang carried out spiritual activities with the theme of the meaning of Muharram as well as providing entrepreneurial motivation for orphans and poor people in the Sabilillah mosque area of Malang. This activity is at the same time providing compensation as a give away for orphans and dhuahas. This activity is expected to make the month of Muharram more meaningful and meaningful by making them happy and encouraging them to rise.